An immunoprophylactic evaluation of Ld-ODC derived HLA-A0201 restricted peptides against visceral leishmaniasis. Issue 13 (21st July 2022) - Pandey, Raj Kishor; Dikhit, Manas Ranjan; Lokhande, Kiran Bharat; Pandey, Krishna; Das, Pradeep; Bimal, Sanjiva
Abstract: Five (5) HLA-A 0201 restricted epitopes of ornithine decarboxylase derived from Leishmania donovani ( Ld- ODC) were examined by reverse vaccinology to develop prophylactics against visceral leishmaniasis (VL). These consensus epitopes comprising (P1: RLMPSAHAI, P2: LLDQYQIHL, P3: GLYHSFNCI, P4: AVLEVLSAL and P5: RLPASPAAL) were observed and presented by diverse HLA alleles screened by immune-informatics tools. These epitopes were also observed for strong stability for appropriate immune response in in silico screening and molecular dynamics. Top five selected epitopes filtered from population coverage analysis and TAP binding affinity were identified and evaluated against treated cases of VL subjects. Experiments were run individually with synthetic peptides or as the cocktail of peptides. A major population of CD8+ T cells were predominantly IFN-γ producers but not the IL-10 cytokines and shown with granzyme-B activity. Therefore, it can be concluded that the screened HLA-A0201 restricted epitope hotspots derived from Leishmania ODC can trigger CD8+ T cells, which can skew other immune cells functions toward protection. However, a detailed analysis can explore its potentiality as a vaccine candidate. Communicated by Ramaswamy H. Sarma